2018
DOI: 10.1016/j.appet.2018.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive defusion and guided imagery tasks reduce naturalistic food cravings and consumption: A field study

Abstract: The present study investigated the effect of two craving reduction techniques, namely, cognitive defusion and guided imagery, on naturalistic food cravings. These techniques targeted the intrusion and elaboration stages of the craving process, respectively (Kavanagh, Andrade, & May, 2005). Participants underwent a seven-day baseline period followed by a seven-day intervention period, during which they recorded their food cravings as they occurred using online diaries accessed via smartphone. In the interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…Of the controlled studies, six ESs were categorized to vivo cue exposure, 39 studies to cognitive regulation strategies (n = 6 acceptance, n = 13 reappraisal, n = 7 suppression, and n = 13 distraction), 13 studies to cognitive control training (n = 3 ICT, n = 4 AAT, and n = 6 ABM), and six to neurofeedback or biofeedback interventions …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the controlled studies, six ESs were categorized to vivo cue exposure, 39 studies to cognitive regulation strategies (n = 6 acceptance, n = 13 reappraisal, n = 7 suppression, and n = 13 distraction), 13 studies to cognitive control training (n = 3 ICT, n = 4 AAT, and n = 6 ABM), and six to neurofeedback or biofeedback interventions …”
Section: Resultsmentioning
confidence: 99%
“…Two studies investigating cue exposure in virtual reality showed medium to huge pre‐post ES on craving . A further study investigated a 7‐day mobile intervention involving distraction and acceptance techniques on craving, both of which had large pre‐post effects on self‐reported craving. A study using suppression‐ and acceptance‐based online self‐help instructions did not have significant effects when comparing baseline with 2‐week postintervention craving scores …”
Section: Resultsmentioning
confidence: 99%
“…Yet, previous research that used comparable craving induction procedures and interference methods successfully showed differences in post-task self-reported craving across experimental conditions (e.g., Andrade, Pears et al, 2012;Kemps & Tiggemann, 2007;May et al, 2010). This was the case, for example, for studies showing the superiority of interference methods in comparison to 'mind wandering' or 'no-task' conditions (e.g., Kemps, Tiggemann, Christianson et al, 2008;May et al, 2012;Schumacher et al, 2018). This observation suggests that the effects obtained in the current study, which followed a similar experimental design to those of the previous studies, can reasonably be attributed to the interference methods and not to the spontaneous reduction of induced craving.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, people high in trait mindfulness have decreased intrusive imagery, are better able to stop their imagery, and can better distract themselves from it (Ostafin, Kassman, & Wessel, 2013). Similarly, guided imagery interventions have similar short-term effects as decentering (Schumacher et al, 2018;Turner & Tapper, 2018). These findings suggest that mindfulness prevents undesired reactions by reducing mental imagery (Tapper, 2018).…”
Section: Introductionmentioning
confidence: 96%